«Սահմանադրութիւն» հասկացութիւնը եւ դրա էութիւնն իրաւունքի եւ քաղաքականութեան փոխգործակցութեան մէջ - Հարությունեան, Արմեն (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена раскрытию понятия и сущности «Конституции» в контексте взаимодействия права и политики. Изучая уже сформировавшиеся подходы к понятию «Конституция» и анализируя роль и значение Конституции в жизни общества и государства, автором был предложен новый подход к понятию «Конституция». В работе также была проанализирована генеалогия слова «Конституция», с помощью которой также была предпринята попытка раскрыть сущность «Конституции. The article is devoted to the disclosure of the concept and essence of the “Constitution” in the context of the interaction between law and politics. Studying the already formed approaches to the concept of “Constitution” and analyzing the role and importance of the Constitution in the life of the society and the state, the author proposed a new approach to the concept of “Constitution”. The paper also analyzed the etymology of the word “Constitution”, with the help of which an attempt was also made to reveal the essence of the “Constitution”.
Keywords: Հաղորդումներ; Սահմանադրութիւն